Correlates of physical activity levels, muscle strength, working memory, and cognitive function in older adults - Li, Shufan; Wang, Peng; Cai, Zhidong; Jiang, Wanting; Xin, Xin; Wang, Xing; Zhou, Xiaojing (Frontiers in Aging Neuroscience, 2023)
Objective: To explore the relationship between physical activity level, muscle strength, working memory and cognitive function in older adults. Methods: A cross-sectional research design was employed to recruit 120 older adults individuals aged 70 and above. Participants were asked to complete the International Physical Activity Questionnaire-Short Form and the Montreal Cognitive Assessment Scale. Data on variables such as grip strength and performance on the N-back task were collected. Data analysis involved the use of independent samples t-tests, χ2 tests, linear regression analysis, Pearson correlation analysis, and one-way analysis of variance (ANOVA). Results: The detection rate of cognitive dysfunction in older adults was 53.211%; 1-back correct rate had an explanatory power of 11.6% for the cognitive function scores of older adults (R2=0.116, P<0.001); grip strength showed a significant positive correlation with 1-back correct rate (r=0.417, P<0.001), and was significantly correlated with the 0-back response time (r=-0.478), 1 -back response time (r=-0.441) were significantly negatively correlated (P<0.001); physical activity level was significantly positively correlated with grip strength (r=0.559, P<0.001), and the difference in grip strength among older adults with different physical activity levels was statistically significant (F=19.685, P<0.001). Conclusion: Physical activity level, muscle strength, working memory, and cognitive function are closely related in older adults, and the relational pathway of physical activity → muscle strength → working memory → cognitive function may serve as a useful addition to promote the field of cognitive research in older adults. To identify and prevent cognitive decline in older adults, physical activity questionnaires, grip strength tests, and 1-back task tests can be extended to nursing homes and communities.